2018
DOI: 10.1590/s1984-296120180060
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Dioctophyme renale larvae (Goeze, 1782) (Nematoda: Enoplida) in a new host from southern Brazil

Abstract: Dioctophymatosis is caused by the giant kidney worm Dioctophyme renale which occurs in dogs, cats, and wild mammals. In Brazil, the disease has been diagnosed in dogs from several states around the country. In the present study, the occurrence of D. renale larvae in snakes from southern of Brazil is reported. Three specimens of Philodryas patagoniensis (Serpentes: Dipsadidae) (common names in Brazil: “parelheira”, “papa-pinto”) roadkill in the county of Capão do Leão, State of Rio Grande do Sul, southern Brazi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 22 publications
0
2
0
1
Order By: Relevance
“…Dioctophyme renale has a vast geographic distribution and has been reported in numerous American, European, and Asian countries (Eiras et al, 2021;Yang et al, 2019). This nematode has been documented throughout Brazil, with emphasis on the southern region of the country, where various studies have reported the adult parasite in dogs and cats (Brunner et al, 2022;Pedrassani et al, 2017;Perera et al, 2016;Rappeti et al, 2017), wild mammals (Pedrassani et al, 2017;Pesenti et al, 2012;Trindade et al, 2018), and paratenic hosts such as anurans (Pedrassani et al, 2009), fish (Mascarenhas et al, 2019), freshwater turtles (Mascarenhas & Müller, 2015;Mascarenhas et al, 2022) and snakes (Mascarenhas et al, 2018). Domestic and wild mammals (definitive hosts) become infected by ingesting infective larva (L3) present in aquatic oligochaetes (intermediate hosts) or fish and anurans (paratenic hosts) (Mace & Anderson, 1975;Measures, 2001;Measures & Anderson, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Dioctophyme renale has a vast geographic distribution and has been reported in numerous American, European, and Asian countries (Eiras et al, 2021;Yang et al, 2019). This nematode has been documented throughout Brazil, with emphasis on the southern region of the country, where various studies have reported the adult parasite in dogs and cats (Brunner et al, 2022;Pedrassani et al, 2017;Perera et al, 2016;Rappeti et al, 2017), wild mammals (Pedrassani et al, 2017;Pesenti et al, 2012;Trindade et al, 2018), and paratenic hosts such as anurans (Pedrassani et al, 2009), fish (Mascarenhas et al, 2019), freshwater turtles (Mascarenhas & Müller, 2015;Mascarenhas et al, 2022) and snakes (Mascarenhas et al, 2018). Domestic and wild mammals (definitive hosts) become infected by ingesting infective larva (L3) present in aquatic oligochaetes (intermediate hosts) or fish and anurans (paratenic hosts) (Mace & Anderson, 1975;Measures, 2001;Measures & Anderson, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, knowing aspects of its ecology and geographical distribution becomes very important for the data production to be used as a basis for bioassessment research and for public health issues, since Lumbriculus variegatus (Müller, 1774) (Lumbriculidae, Clitellata) was identified in as the intermediate host of Dioctophyme renale (Goeze, 1782) (Nematoda, Dioctophymatidae) (Mace and Anderson, 1975). Dioctophyme renale has a worldwide distribution and can affect dogs, cats, wild mammals and even human (Mascarenhas et al, 2018) being characterized as zoonosis (Pedrassani and Nascimento, 2015). The life cycle of parasite occurs through the ingestion of eggs by Lumbriculus variegatus, which is the only intermediate host essential for the continuation of the cycle.…”
mentioning
confidence: 99%
“…oligoqueto de agua dulce y éste puede ser ingerido por ranas, peces de agua dulce, tortugas dulceacuícolas y culebras, que sirven como hospedadores paraténicos (Mace & Anderson 1975;Measures 2001;Pedrassani et al 2009;Mascarenhas & Muller 2015;Mascarenhas et al 2018Mascarenhas et al , 2019. Los nemátodos presentan una coloración característica (rojo/púrpura oscuro) (Giorello et al 2017) y en cánidos domésticos su longitud varía, con un tamaño en hembras hasta 100 cm y en machos entre 11-30 cm (Urquhart et al 1998;Measures 2001;Taylor et al 2016).…”
unclassified